Prompt Identification of Congenital Heart Disease by Echocardiographic Screening - Stephen Rottile (Akademi Sertifikasi Profesi Internasional, 2024)
Congenital cardiac disease is the most prevalent congenital condition responsible for the highest mortality rate. Insufficient information among healthcare professionals hinders preventative and early detection efforts. We must implement educational initiatives designed to enhance the expertise of healthcare professionals in early identification and intervention. This initiative encompasses webinar training and echocardiography screening conducted with healthcare professionals in Kediri. We evaluated the participant's knowledge through a pre-test and post-test. A consultant pediatrician does an echocardiography screening next. A total of 451 participants attended the webinar. The mean pre-test score is 5.80 out of 15, whereas the mean post-test score is 12.84 out of 15. A total of 29 children underwent echocardiographic examination. Nineteen (65.52%) children were diagnosed with Asiatic congenital heart disease, four (13.79%) with cyanotic conditions, and six (20.68%) were classified as normal. Webinar training enhances health workers' understanding of early detection, with 79.31% of children undergoing echocardiography screening receiving a diagnosis